Qualitative Analysis for a Predator Prey System with Holling Type III Functional Response and Prey Refuge - Xia Liu; Yepeng Xing (Discrete Dynamics in Nature and Society, 2012)
A predator prey system with Holling III functional response and constant prey refuge is considered. By using the Dulac criterion, we discuss the global stability of the positive equilibrium of the system. By transforming the system to a Liénard system, the conditions for the existence of exactly one limit cycle for the system are given. Some numerical simulations are presented.